Combating social determinants with collective weapons: Social identities and health inequalities in Portuguese veterans - Romão, Â.; Lima, M. L.; Moleiro, C.; António, R.; Moura, R. (Journal of Military Veteran and Family Health, 2026)
Introduction: Exposure to traumatic experiences during military service can result in different psychological and social consequences for individuals and their close social networks. This study aims to contribute to a psychosocial understanding of these phenomena by examining whether the relationship between perceived socio-economic status and the health of Veterans is moderated by participation in Veterans’ associations, as well as whether this moderation effect is moderated by the level of identification with the military group. Methods: A total of 480 Portuguese Veterans (Mage = 73.24; SD = 3.74) completed validated measures of perceived socio-economic status, physical and mental health, identification with the military, and participation in Veterans’ associations. Results: The results show that Veterans facing greater economic vulnerability report poorer health outcomes. However, those who are members of Veterans’ associations, particularly those with a strong identification with the military, report better health despite their socio-economic vulnerability. Discussion: Overall, this study highlights the importance of Veterans’ associations as identity-based support networks that can promote the health and well-being of military Veterans.